Staying, leaving, or seeking more: International students’ post-graduation settlement and migration decisions in South Korea - Feyissa, Israel Fisseha; Sherpa, Sonam (Journal of International Students, 2025)
Amid South Korea’s demographic decline and push for global talent retention, this study examines the factors that drive international students to stay or migrate in search of opportunities elsewhere. This study unpacks the complex web of factors—academic satisfaction, social integration, career aspirations, financial support, and participation in the Korean Immigration and Integration Program (KIIP)—that shape post-graduation settlement intentions. Analyzing data from 286 students in Busan’s private universities, the results show career awareness and financial security as powerful motivators. Ironically, social integration and KIIP participation wield little influence. Life satisfaction emerges as a mediator, revealing that staying isn’t just about opportunity—it’s about belonging.